Human Rights in the Distribution of Vaccines Against Civilians According to International Law: An Analysis of Human Rights Problems in the Acceptance of Vaccines COVID-19 in Philippines - Nursabila, Arivania Shafa; Rifana, Ruri (International Law Department, Faculty of Law Universitas Padjadjaran, 2024)
In an effort to boost the Philippines' economic recovery amidst the COVID-19 pandemic, the government made the decision in January 2022 to allow foreign tourists to enter the country without the need for quarantine, as long as they can provide proof of vaccination. However, some Filipinos have expressed discontent with this choice, as unvaccinated individuals continue to face travel difficulties. Addressing this issue, President Rodrigo Duterte has warned that those who choose not to get vaccinated and violate stay-at-home orders may face arrest. Extensive analysis and literature review have revealed that vaccination is a communal right. While the decision to receive a vaccine is a personal choice, legal principles dictate that every individual has the right to choose what substances are introduced into their body. However, in cases where there is a high risk of contagion, such as with Covid-19, governments may mandate the distribution of vaccines for public safety. This conclusion is based on an evaluation of international legal instruments, including the UDHR, ICCPR, ICESCR, and others.